The Effectiveness of Using Flipbook E-Module With Flipped Classroom-Integrated Problem-Based Learning Model On Student Understanding - Afni, Nur; Nur, Andi Bulqiah (MACCA : Science-Edu Journal, 2024)
This study aims to evaluate the effectiveness of using the flipbook e-module with flipped classroom-integrated Problem-Based Learning (PBL) model in the Pharmaceutical Chemistry course. This e-module was tested on 20 students by comparing the results of the pretest and posttest using the N-Gain Score. The results showed that the e-module was able to increase the average understanding of students based on an increase in value from 51 (pretest) to 77.5 (posttest), with an average N-Gain Score of 0.55 which is included in the moderate category. These findings indicate that the e-module is quite effective in improving student understanding. The study recommends further development to improve learning effectiveness.